Hipoglikemia Persisten pada Pasien Non-Diabetes dalam Kondisi Kritis: Mengungkap Penyebab yang Tidak Terkait dengan Insulin — Laporan Kasus: Laporan Kasus - Pamungkas, Kadek Mercu Narapati; Suryana, I Ketut (Cermin Dunia Kedokteran, 2026)
Introduction: Hypoglycemia is uncommon in patients without diabetes mellitus, yet critical illness can precipitate it through impaired gluconeogenesis and depletion of hepatic glycogen stores. When this occurs in the absence of insulin therapy or a diabetic history, identifying the underlying cause becomes a diagnostic challenge. Case: A 56-year-old male presented with decreased consciousness secondary to severe hypoglycemia (glucose 42 mg/dL). He had a history of suspected metastatic stage IV prostate cancer with a markedly elevated prostatespecific antigen (PSA) of 930.8 ng/mL, severe anemia (Hb 4.9 g/dL), transaminitis (aspartate aminotransferase/AST 108 U/L), and a normal HbA1c of 4.7% with no prior history of diabetes mellitus. During hospitalization, he was additionally diagnosed with complicated urinary tract infection and hospital-acquired pneumonia. By day three, persistent recurrent hypoglycemia developed despite glucose supplementation. On day five, the patient deteriorated into type 2 respiratory failure requiring ICU admission, and subsequently died. Discussion: Persistent hypoglycemia in this patient was likely multifactorial, involving tumor-related mechanisms, critical illness with concurrent infections, hepatic dysfunction, and prolonged malnutrition, whereas normal HbA1c and the absence of glycosuria excluded underlying diabetes mellitus and renal glucose wasting. Conclusion: This case underscores that persistent hypoglycemia in critically ill non-diabetic patients is a clinically important and often diagnostically elusive condition. A multifactorial approach encompassing malignancy-related mechanisms, hepatic dysfunction, sepsis, and nutritional depletion is essential for timely recognition and management.